Energetic Constraints on the Intertropical Convergence Zone Position in the Observed Seasonal Cycle From Modern‐Era Retrospective Analysis for Research and Applications, Version 2 (MERRA‐2). Issue 16 (24th August 2020) - Wei, Ho‐Hsuan; Bordoni, Simona
Abstract: Idealized simulations show that the approximate colocation between the ITCZ and the energy flux equator (EFE), which holds on the annual and zonal average, breaks down on subseasonal timescales, as the Hadley cell develops a shallow return flow and negative gross moist stability (GMS). Here, we explore if similar mechanisms are seen in reanalysis data. In the zonal mean, a temporal offset exists between the ITCZ and the EFE as the ITCZ is retreating from the Northern to Southern Hemisphere and the Hadley cell transports energy northward across the equator despite a northward‐shifted ITCZ. At these times, the southern cell has a bottom‐heavy structure, with a distorted cell boundary and northward energy transport. In the Eastern Pacific, while bottom‐heavy structures exist throughout the year, the bottom heaviness is stronger in boreal fall, when GMS is negative, and SSTs are weak while their Laplacian is large and negative below the ITCZ. Plain Language Summary: The intertropical convergence zone (ITCZ) is a narrow band of intense rainfall near the equator. What controls the position of the ITCZ on different timescales is a question that remains open in the literature. In the past decade, it has been argued that the tropical overturning circulation transports energy away from the ITCZ and, hence, the annual and zonal mean ITCZ is approximately colocated with the latitude at which the energy transport vanishes (the energy flux equator, EFE). Idealized numerical simulations, however, show that this relationship might break down on subseasonal timescales. Here, we use reanalysis data to explore if and why this also happens in the observed seasonal cycle. We find that in the zonal mean, the EFE and the ITCZ are located on opposite sides of the equator in boreal fall and winter, with the cross‐equatorial southern Hadley circulation having a bottom‐heavy structure that favors energy transport in the direction of the lower‐level flow, and hence into rather than away from the ITCZ. In the Eastern Pacific, bottom‐heavy circulation profiles persist throughout the year but are stronger when the ITCZ and the EFE are in opposite hemispheres and when the meridional curvature of the SST distribution is large. Key Points: The energy flux equator and the ITCZ are not colocated in the observed seasonal cycle The breakdown of this relationship is due to changes in the bottom heaviness of vertical motions This is especially evident in the Eastern Pacific and is related to the spatial distribution of sea surface temperatures